Challenges and promise of targeting miRNA in rheumatic diseases: a computational approach to identify miRNA association with cell types, cytokines, and disease mechanisms - Shaikh, Farheen S.; Siegel, Ruby J.; Srivastava, Aayush; Fox, David A.; Ahmed, Salahuddin (Frontiers in Immunology, 2024)
MicroRNAs (miRNAs) are small non-coding RNAs that alter the expression of target genes at the post-transcriptional level, influencing diverse outcomes in metabolism, cell differentiation, proliferation, cell survival, and cell death. Dysregulated miRNA expression is implicated in various rheumatic conditions, including ankylosing spondylitis (AS), gout, juvenile idiopathic arthritis (JIA), osteoarthritis (OA), psoriatic arthritis, rheumatoid arthritis (RA), Sjogren's syndrome, systemic lupus erythematosus (SLE) and systemic sclerosis. For this review, we used an open-source programming language-PowerShell, to scan the massive number of existing primary research publications on PubMed on miRNAs in these nine diseases to identify and count unique co-occurrences of individual miRNAs and the disease name. These counts were used to rank the top seven most relevant immuno-miRs based on their research volume in each rheumatic disease. Individual miRNAs were also screened for publication with the names of immune cells, cytokines, and pathological processes involved in rheumatic diseases. These occurrences were tabulated into matrices to identify hotspots for research relevance. Based on this information, we summarize the basic and clinical findings for the top three miRNAs -miR-146, miR-155, and miR-21 -whose relevance spans across multiple rheumatic diseases. Furthermore, we highlight some unique miRNAs for each disease and why some rheumatic conditions lack research in this emerging epigenetics field. With the overwhelming number of publications on miRNAs in rheumatic diseases, this review serves as a 'relevance finder' to guide researchers in selecting miRNAs based on the compiled existing knowledge of their involvement in disease pathogenesis. This approach applies to other disease contexts with the end goal of developing miRNA-based therapeutics.